Ethics of therapeutic relationship in psychiatry - Binetti, Paola (Medicina e Morale, 2000)
Ethics submits a number of very specific issued to psychiatry which can be synthetized in the following triad: definition of the anthropological reference frame; quality criteria identification of a therapeutic relation; awareness that the patient's environment is an element of suffering as well as an irremissible resource. Each time these three aspects can answer the following questions form a multifocal point of view: Who is the patient? Who are we within the doctor patient relationship? Who are they within the social and family environment? The decisional models which derive from reciprocal knowledge and respect, are ethically acceptable because they are centred on the common wellbeing. However in psychiatry the manipulation of the therapeutic relationship is a constant risk arising from the essential mistrust of the other person's competence and managing event's correctly. In psychiatry truth and error have to be analysed considering the real individual conditions, the gradual progress, and the many attempts and mistakes man makes in approaching knowledge. Besides, in the psychiatric relationship another irremissible aspect is the one which allows the patient's genuine expression avoiding family or health staff inappropriate substitutions. Such authenticity, typical expression of one's own identity, is among the most important and effective therapeutic factor as it is accepted by the patients as well as by who undertakes their suffering. A decision ha to be made freely and has to respect the subject's conscience to be ethically acceptable. For this reason it is essential that the help offered allows the patient to make free choices and gradually understand their importance through the consequences in real life. Freedom has to be considered as a continuous achievement, which the psychiatrist safeguards from false manipulations, in a relationship with a psychiatric patient. The issue of the relationship between ethics as a personal responsibility, and objectivity as a universal frame of reference, is made clear only if one considers it from the human rights point of view: the right to know the truth; the right to make coherent choices; the righ to obtain the necessary help so as to redeem one's freedom from various kinds of conditioning. In other words: to undertake the principle of personal autonomy as the basis of the psycho-therapeutic help relationship, even when such autonomy, considered as a right, has to be supported up to the point of becoming responsibility towards oneself as well as towards others.